Management of Age Diversity at the Workplace - Rožman, Maja; Tominc, Polona (Naše gospodarstvo/Our economy, 2014)
The aging population in Slovenia is one of the biggest challenges for the future de- velopment and also affects the processes within organizations. The basic purpose of this paper is to examine employees’ age diversity based on motivating factors, job satisfaction, and productivity. In this study, we find many differences in the influ- ence of motivational factors between younger and older employees, the degree of their satisfaction, and other areas related to the dynamics, diversity, and producti- vity of employees in the workplace. These findings also suggest the importance of managing age diversity in the workplace; thus, we provide some recommendations for management.
Keywords: motivational factors; employee satisfaction; age diversity